2011
DOI: 10.1007/s11999-010-1670-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Nonoperatively Treated Displaced Scapular Body Fractures

Abstract: Background Displaced scapular body fractures most commonly are treated conservatively. However there is conflicting evidence in the literature regarding the outcomes owing to retrospective design of studies, different classification systems, and diverse outcome tools. Questions/purposes The functional outcome after nonoperative management of displaced scapular body fractures was assessed by change in the DASH (Disability of Arm, Shoulder and Hand) score; (2) the radiographic outcome was assessed by the change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 37 publications
0
25
0
1
Order By: Relevance
“…In the international literature, the indication for treating scapula body fractures surgically is controversially discussed and poor to excellent results have been shown in both conservative and surgical treatment [31,32]. Different aspects such as outcome, pain, non-union, and surgical approach were analyzed as well as advantages and disadvantages of ORIF in contrast to conservative treatment of scapula body Fx [2,8,28,[33][34][35][36]. None of these studies gave thought to the fact that poor outcome, pain, and limited range of motion might result from concomitant intra-articular glenohumeral injuries.…”
Section: Discussionmentioning
confidence: 99%
“…In the international literature, the indication for treating scapula body fractures surgically is controversially discussed and poor to excellent results have been shown in both conservative and surgical treatment [31,32]. Different aspects such as outcome, pain, non-union, and surgical approach were analyzed as well as advantages and disadvantages of ORIF in contrast to conservative treatment of scapula body Fx [2,8,28,[33][34][35][36]. None of these studies gave thought to the fact that poor outcome, pain, and limited range of motion might result from concomitant intra-articular glenohumeral injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Hardegger, Ada and Miller, Nordquist, and Petersson felt that translation of the neck resulted in altered mechanics and weakening of the rotator cuff, shoulder dysfunction, and pain. Multiple other studies have also reported good functional outcomes with nonoperative treatment of moderately displaced fractures (Jones and Sietsema, 2011;Schofer et al, 2009;Gosens et al, 2009;Dimitroulias et al, 2011). Chadwick et al has given support to this theory by demonstrating in a lab model that a change in moment arm from a simulated malunion of a scapula fracture results in increased work by the rotator cuff, pectoralis, and bicep muscles (Chadwick et al, 2004).…”
Section: Intraarticular Glenoid Fracturesmentioning
confidence: 95%
“…En general, el manejo de las fracturas de escápula es conservador, como lo demuestra el estudio de Dimitroulias y su equipo, 5 el cual indica que los resultados con tratamiento conservador son satisfactorios en la escala de DASH, reservándose el manejo quirúrgico a aquéllas desplazadas más de 20 mm y con angulaciones mayores de 45 o , al igual fracturas intraarticulares de la glenoides con desplazamientos mayores de 4 mm y/o más de 20% de afección de la superficie glenoidea, 6 la cual puede ser manejada por artroscopia. [5][6][7]…”
Section: Fractura De Espina Del Omóplatounclassified